Homozygous Mutation of gsdf Causes Infertility in Female Nile Tilapia (Oreochromis niloticus) - Jiang, Dong-Neng; Peng, You-Xing; Liu, Xing-Yong; Mustapha, Umar Farouk; Huang, Yuan-Qing; Shi, Hong-Juan; Li, Ming-Hui; Li, Guang-Li; Wang, De-Shou (Frontiers in Endocrinology, 2022)
Gonadal somatic cell-derived factor (Gsdf) is a member of the TGF-β superfamily, which exists mainly in fishes. Homozygous gsdf mutations in Japanese medaka and zebrafish resulted in infertile females, and the reasons for their infertility remain unknown. This study presents functional studies of Gsdf in ovary development using CRISPR/Cas9 in Nile tilapia (Oreochromis niloticus). The XX wild type (WT) female fish regularly reproduced from 12 months after hatching (mah), while the XX gsdf -/- female fish never reproduced and were infertile. Histological observation showed that at 24 mah, number of phase IV oocyte in the XX gsdf -/- female fish was significantly lower than that of the WT fish, although their gonadosomatic index (GSI) was similar. However, the GSI of the XX gsdf -/- female at 6 mah was higher than that of the WT. The mutated ovaries were hyperplastic with more phase I oocytes. Transcriptome analysis identified 344 and 51 up- and down-regulated genes in mutants compared with the WT ovaries at 6 mah. Some TGF-β signaling genes that are critical for ovary development in fish were differentially expressed. Genes such as amh and amhr2 were up-regulated, while inhbb and acvr2a were down-regulated in mutant ovaries. The cyp19a1a, the key gene for estrogen synthesis, was not differentially expressed. Moreover, the serum 17β-estradiol (E2) concentrations between XX gsdf -/- and WT were similar at 6 and 24 mah. Results from real-time PCR and immunofluorescence experiments were similar and validated the transcriptome data. Furthermore, Yeast-two-hybrid assays showed that Gsdf interacts with TGF-β type II receptors (Amhr2 and Bmpr2a). Altogether, these results suggest that Gsdf functions together with TGF-β signaling pathway to control ovary development and fertility. This study contributes to knowledge on the function of Gsdf in fish oogenesis.